Recall of “The Real Cost” Anti-Smoking Campaign Is Specifically Associated With Endorsement of Campaign-Targeted Beliefs - Kranzler, Elissa C. (J Health Commun, 2017)
Though previous research suggests the FDA's “The Real Cost” anti-smoking campaign has reduced smoking initiation, the theorized pathway of effects (through targeted beliefs) has not been evaluated. This study assesses the relationship between recall of campaign television advertisements and ad-specific anti-smoking beliefs. Respondents in a nationally representative survey of nonsmoking youths age 13–17 (n = 4,831) reported exposure to four The Real Cost advertisements and a fake ad, smoking-relevant beliefs, and nonsmoking intentions. Analyses separately predicted each targeted belief from specific ad recall, adjusting for potential confounders and survey weights. Parallel analyses with non-targeted beliefs showed smaller effects, strengthening claims of campaign effects. Recall of four campaign ads (but not the fake ad) significantly predicted endorsement of the ad-targeted belief (Mean β = .13). Two-sided sign tests indicated stronger ad recall associations with the targeted belief relative to the non-targeted belief (p < .05). Logistic regression analyses indicated that respondents who endorsed campaign-targeted beliefs were more likely to have no intention to smoke (p < .01). This study is the first to demonstrate a relationship between recall of ads from The Real Cost campaign and the theorized pathway of effects (through targeted beliefs). These analyses also provide a methodological template for showing campaign effects despite limitations of available data.